Gesprekken met mormoonse vrouwen in Vlaanderen: Omgaan met structurele ambivalentie - Decoo, Ellen; Longman, Chia (Religie & Samenleving, 2021)
Latter-day Saints (Mormons) living outside the ‘Mormon Culture Region’ in the Western United States usually form small minorities. As Mormonism upholds conservative gender norms, we investigated how a sample of thirteen Mormon women living in Flanders (Northern part of Belgium) experienced their relation with the Flemish secular-liberal environment. The research used the framework of structural ambivalence to assess how these women cope with conflicting norms on marriage age, male-only priesthood and familial dilemmas. Results show how respondents use arguments and strategies to handle or to avert ambivalence.